Atmospheric induced nanoparticles due to the urban street dust. (2nd September 2016) - Paltinean, Alexandra Gertrud; Petean, Ioan; Arghir, George; Muntean, Dana Florina; Bobos, Liviu-Dorel; Tomoaia-Cotisel, Maria
ABSTRACT: Urban street dust (SD) represents a natural source of mineral floating particles (FP) in the atmosphere. The FP particles have usually a wide range of sizes. These particles were monitored and collected by automatic stations in Cluj-Napoca, Romania. The SD and FP samples were investigated by XRD and SEM-EDX analysis. The obtained results prove that both, SD and FP, have a similar composition, namely quartz, clay particles (e.g., muscovite, and kaolinite), calcite, and trace of lepidocrocite. Nanostructural features and fine micro-scaled particles are observed. Quartz and clay nanoparticles were found in SD samples as well as in FP samples. The AFM investigation reveals a nano-size range for quartz particles between 80–90 nm, and 40–60 nm diameter for clay particles. Similar values were obtained by TEM microscopy. The high resolution microscopy results were confirmed by the values obtained by Scherrer formula applied to the XRD patterns. Composition and dimensional similarities found for the nanoparticles in SD and FP samples prove that mineral nanofractions in atmosphere were induced by the urban environmental interactions with the SD. Results provide valuable information on the size, shape, and composition of nanoparticles induced in atmosphere by winds and by environmental interactions with the SD. This work contributes to the evaluation of the air pollution and simultaneously it offers a basis for an improved life quality for Cluj-Napoca population.